Suppressor of cytokine signaling 1 expression during LPS-induced inflammation and bone loss in rats - João Antonio Chaves de SOUZA; Andressa Vilas Boas NOGUEIRA; Pedro Paulo Chaves de SOUZA; Guilherme José Pimentel Lopes de OLIVEIRA; Marcell Costa de MEDEIROS; Gustavo Pompermaier GARLET; Joni Augusto CIRELLI; Carlos ROSSA JUNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This study aimed to characterize the dynamics of suppressor of cytokine signaling (SOCS1) expression in a rat model of lipopolysaccharide-induced periodontitis. Wistar rats in the experimental groups were injected three times/week with LPS from Escherichia coli on the palatal aspect of the first molars, and control animals were injected with vehicle (phosphate-buffered saline). Animals were sacrificed 7, 15, and 30 days after the first injection to analyze inflammation (stereometric analysis), bone loss (macroscopic analysis), gene expression (qRT-PCR), and protein expression/activation (Western blotting). The severity of inflammation and bone loss associated with LPS-induced periodontitis increased from day 7 to day 15, and it was sustained through day 30. Significant (p < 0.05) increases in SOCS1, RANKL, OPG, and IFN-γ gene expression were observed in the experimental group versus the control group at day 15. SOCS1 protein expression and STAT1 and NF-κB activation were increased throughout the 30-day experimental period. Gingival tissues affected by experimental periodontitis express SOCS1, indicating that this protein may potentially downregulate signaling events involved in inflammatory reactions and bone loss and thus may play a relevant role in the development and progression of periodontal disease.